AB0472 Pharmacodynamic effect and safety of single-dose sarilumab sc or tocilizumab iv or sc in patients with rheumatoid arthritis (RA). (12th June 2018) - Ishii, T.; Sato, Y.; Munakata, Y.; Kajiwara, M.; Takahashi, Y.; Anwar, F.; Paccaly, A.; Kovalenko, P.; Parrino, J.; Boyapati, A.; Xu, C.
Abstract : Background: Two studies (PDY14191 [NCT02404558 ]: randomised, open-label, Japanese patients; 6R88-RA-1309 [NCT02097524 ]: randomised, open-label, non-Japanese patients) assessed the pharmacodynamic profiles of two monoclonal antibody blockers of IL-6Rα, sarilumab and tocilizumab. Objectives: To evaluate the pharmacodynamics of absolute neutrophil count (ANC), C-reactive protein (CRP), IL-6, soluble IL-6R (sIL-6R), and safety after a single dose of subcutaneous (SC) sarilumab, or intravenous (IV) or SC tocilizumab in patients with RA. Methods: 30 Japanese patients (PDY14191) were randomised 1:1 and received a single injection with SC sarilumab 150 mg or SC tocilizumab 162 mg without background medication. 101 non-Japanese patients (6R88-RA-1309) were randomised 1:1:1:1 and received a single dose of SC sarilumab (150 or 200 mg)+methotrexate (MTX), or IV tocilizumab (4 or 8 mg/kg)+MTX. Pharmacodynamic and safety outcomes were assessed through Week 6. Results: Baseline demographics were comparable between studies except for higher mean body weight in non-Japanese patients (mean 83 vs 57 kg). Although there were numeric differences in baseline pharmacodynamic parameters in the two studies, onset of effects on ANC, CRP, IL-6, and sIL-6R during the first week after a single drug dose were similar regardless of drug, dose, or route of administration in both studies. Within both studies, maximal effects on ANC and CRP nadir and on IL-6 and total sIL6-R peaks were comparable for sarilumab and tocilizumab (table 1). The pharmacodynamic response was more prolonged with IV tocilizumab. Time for pharmacodynamic effects to return to baseline was consistent with the dosing intervals for SC sarilumab (q2w), and IV (q4w) and SC (q2w) tocilizumab. The safety profiles of sarilumab and tocilizumab were generally similar and both drugs were associated with laboratory effects consistent with their mechanism of action (ie, decrease in neutrophil count). There was a dose-dependent effect on ANC<1.0 Giga/L in study 6R88-RA-1309 and numeric differences in ANC<1.0 Giga/L between sarilumab and tocilizumab in PDY14191. The decrease in ANC was not associated with increased risk of infections. Conclusions: The pharmacodynamic and safety profiles observed after a single-dose of sarilumab SC or IV/SC tocilizumab are consistent with results anticipated in patients with RA administered an IL–6R inhibitor. Acknowledgements: Study funding and medical writing support (Julie Grey, Adelphi Group) was provided by Sanofi and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: T. Ishii Paid instructor for: GSK, Janssen, Speakers bureau: Mitsubishi-Tanabe, Janssen, Chugai, Ono, Sanofi, Abbvie, Eisai, Astellas, UCB, Teijin, Daiichi-Sankyo, Pfizer, Takeda, Asahi Kasei Pharma, Y. Sato Consultant for: SRL, Paid instructor for: Bristol-Myers Squibb, Y. Munakata: None declared, M. Kajiwara Employee of: Sanofi K.K., Y. Takahashi Employee of: Sanofi K.K., F. Anwar Employee of: Sanofi, A. Paccaly Shareholder of: Regeneron, Sanofi, Amgen, Employee of: Regeneron, P. Kovalenko Shareholder of: Regeneron, Employee of: Regeneron, J. Parrino Shareholder of: Regeneron, Employee of: Regeneron, A. Boyapati Shareholder of: Regeneron Pharmaceuticals, Employee of: Regeneron Pharmaceuticals, C. Xu Shareholder of: Sanofi, Employee of: Sanofi